Design Optimization of Thermal Management System for Electric Vehicle Utilizing CFD Analysis, DFMEA and CES - tamaldin, noreffendy; Mat Yamin, Ahmad Kamal; Abdollah, Mohd Fadzli bin; Amiruddin, Hilmi; ABDULLAH, Mohd Azman (2014)
Thermal management design for electric vehicles (EV) is very important in order to manage the thermal dissipated by operating components. This research aims at performing design optimization of a thermal management system for battery modules, controller and electric motor in EV. A combination of passive and active cooling systems is proposed where air cooled is used in battery modules, water cooling for controller and water jacket for electric motor. Design Failure Mode and Effect Analysis (DFMEA) method is deployed to identify the potential failure modes and causes so that improvements can be made for battery modules, controller and electric motor. The design for all of the components and the thermal management system were done with CATIA V5. The material selections process for the designs was based on the analysis using Cambridge Engineering Selector (CES EduPack). Final design was utilizing water cooled for electric motor and controller while using air cooled for battery modules. It was found that best material for electric motor and controller water jacket is with aluminum alloy 6060 while air cooled ducting using High Density Poly Ethylene (HDPE) and battery housing using Polycyclohexylenedimethylene Terephthalate (PCT). The thermal management system for battery modules is simulated using ANSYS CFD software. Results from simulation were validated with manual calculation and have shown good agreement based on the data collected at various vehicle speeds.